The Spine Raptor—a new genus of predatory katydid (Orthoptera: Tettigoniidae: Meconematinae: Phlugidini) from the Brazilian Amazon Rainforest - Mendes, Diego Matheus De Mello; Sobral, Rafael; Neto, Alberto Moreira Da Silva (Zootaxa, 2024)
The Phlugidini tribe (Meconematinae: Tettigoniidae) currently comprises 10 genera and 64 species of small predatory katydids with Neotropical distribution. Herein, we describe the new genus Spinaraptor gen. nov. with five species included: Spinaraptor taja sp. nov. (type species), Spinaraptor celerinicta (Nickle, 2003) comb. nov., Spinaraptor ecuador (Gorochov, 2012) comb. nov., Spinaraptor gerana (Gorochov, 2015) comb. nov. and Spinaraptor nemoptera (Bolivar, 2012) comb. nov. (All transferred from Phlugis Stål, 1861). Pictorial keys to species in the genus, maps and natural history observations are provided.